2014
DOI: 10.1016/j.breast.2014.02.009
|View full text |Cite
|
Sign up to set email alerts
|

The impact of educational materials on compliance and persistence rates with adjuvant aromatase inhibitor treatment: First-year results from the Compliance of ARomatase Inhibitors AssessmenT In Daily practice through Educational approach (CARIATIDE) study

Abstract: The CARIATIDE study was designed to assess the impact of educational materials (EMs) on compliance and persistence rates with aromatase inhibitor (AI) treatment in postmenopausal women with hormone-receptor-positive early breast cancer. Patients were randomized to standard AI treatment (Group A; N = 1379) or standard AI treatment plus EMs containing information on a range of breast-cancer-related topics (Group B; N = 1379). Standardized questionnaires assessed investigator-perceived levels of care and evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 31 publications
1
61
0
1
Order By: Relevance
“…In relation to the interventions, three of the studies tested the German-based PACT study intervention but in different contexts. 14, 24, 25 In relation to the study design, 80% (n=4) of the papers consisted of randomized controlled trials (RCT; n=4), all included an educational component (100%; n=5), and 60% incorporated reminders (n=3). All interventions were targeted towards patients (100%; n=5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In relation to the interventions, three of the studies tested the German-based PACT study intervention but in different contexts. 14, 24, 25 In relation to the study design, 80% (n=4) of the papers consisted of randomized controlled trials (RCT; n=4), all included an educational component (100%; n=5), and 60% incorporated reminders (n=3). All interventions were targeted towards patients (100%; n=5).…”
Section: Resultsmentioning
confidence: 99%
“…Adjuvant hormonal therapy adherence and persistence were expressed as proportions and were either abstracted 14, 24 or calculated 25, 26 based on reported data by two authors (TL and CD). Odds ratios (OR) and its 95% CI comparing adherence and persistence with adjuvant hormonal therapy in the intervention compared to the usual care group were also calculated from study results and are presented in Tables 3 and 4.…”
Section: Methodsmentioning
confidence: 99%
“…451 Other studies have noted no improvement in patients given additional education materials or increased support services. 452,453 Going forward, technologic advances such as the widespread use of electronic medical records, sophisticated prescription bottles with built-in reminder timers, and effective pharmacy tracking systems may lead to further improvements. Simplified dosing regimens, as well as seamless access to refills, may also help improve compliance.…”
Section: Original Research and Contributionsmentioning
confidence: 99%
“…Five of these studies were randomized trials, none of which demonstrated significant differences between the intervention and control groups with respect to their primary adherence outcomes [44,45,47,52,54]. One randomized, three-arm trial did show differences in adherence, favoring the intervention groups, when the investigators conducted a post hoc pooled analysis comparing both interventions to the control group [47].…”
Section: Interventions To Improve Adherence To Oral Antineoplastic Thmentioning
confidence: 99%
“…In a total of 12 studies ( [44][45][46][47], treatment monitoring [48], pharmacy-based programs [42,49,50], counseling programs [51,52], prefilled pill boxes [53], and automated voice response systems [54]. Five of these studies were randomized trials, none of which demonstrated significant differences between the intervention and control groups with respect to their primary adherence outcomes [44,45,47,52,54].…”
Section: Interventions To Improve Adherence To Oral Antineoplastic Thmentioning
confidence: 99%